EXAMINATION OF CHANGING PARADIGMS AND HEALING HOSPITAL CONCEPT IN HEALTHCARE FACILITIES WITH REGARD TO ARCHITECTURAL DESIGN - Ergenoglu, Asli Sungur; Aytug, Ayfer (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2007)
In the recent years, significant changes have started to occure in the healthcare sector. Developments in the area of healing hospital design and accreditation have been accelerating. In the paper, the probable reflections of the new paradigms, approaches and insights that effect hospital design have been examined. Furthermore, the effects of hospital buildings and environments on patient well-being are described. The properties that hospitals should have in order to become buildings that are used for everyday purposes and contribute to the healing process with their physical characteristics are put forward. In this context, the 'healing hospital' concept, not only contributing to healing process, but also armed with the ability to pull the society to itself in healthy times, user contribution in healing hospitals, the properties of patient-focused design and quality concept are examined. The criteria developed for hospital design have to include environmental standards and quality issues, together with the spatial standards and technical details. Hospital accreditation subject that has been gaining importance in the recent years will play a significant role in hospital quality in the future. The patient-focused design criteria should be included to the accreditation standarts immediately. Hospital buildings have to raise the life and care quality, offer solutions that will be able to affect the patient well-being directly and be trusted with its compatibility to the accreditation standarts with a patient-focused mind.
Keywords: architecture and medicine; patient-focused design; accreditation; quality; user contribution; Architecture